2015
DOI: 10.5489/cuaj.2783
|View full text |Cite
|
Sign up to set email alerts
|

An integrative review and severity classification of complications related to pessary use in the treatment of female pelvic organ prolapse

Abstract: Introduction: Pessary use is the preferred non-surgical treatment option for female pelvic organ prolapse. As pessaries can be used chronically to alter pelvic floor anatomy, consideration of shortand long-term complications is important in patient management. We systematically reviewed articles describing the complications of pessary use to determine frequency and severity. Methods: A systematic search via MEDLINE and PubMed using the key terms "complications," "pessary," "pelvic organ prolapse," "side effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
1
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 71 publications
1
79
1
6
Order By: Relevance
“…4,5,7 A systematic review showed that vaginal discharge is the most frequent complication related to the use of pessary, occurring in 56% of the users. 6 The results of this study showed that vaginal discharge is very common in women With regard to the vaginal content of the women included in this study, it can be observed that there was no difference between the types of flora in both groups. A recent study assessing the flora before and after one month of use of pessary also showed that the vaginal flora is not always changed by the use of pessary.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…4,5,7 A systematic review showed that vaginal discharge is the most frequent complication related to the use of pessary, occurring in 56% of the users. 6 The results of this study showed that vaginal discharge is very common in women With regard to the vaginal content of the women included in this study, it can be observed that there was no difference between the types of flora in both groups. A recent study assessing the flora before and after one month of use of pessary also showed that the vaginal flora is not always changed by the use of pessary.…”
Section: Discussionmentioning
confidence: 59%
“…1,3 It is a minimally invasive device and presents low risk, but it can show some complications. 6,8 For instance, vaginal discharge is the primary adverse effect of women using pessary. 6,8 Currently, there are scant data on the use of this device and the possible symptoms associated with its use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Device removal and the use of topical oestrogen was successful in reversing these types of early cytological changes [201]. Foreign body reaction and chronic inflammation have been associated with several cervical and vaginal cancers occurring at the sites of pessary insertion, but the absolute number of cases remains too low to properly evaluate [207,210].…”
Section: Histologymentioning
confidence: 99%
“…Overall, pessary use is comfortable, effective, and low risk; however, serious adverse events such as vesicovaginal/rectovaginal fistula and incarcerated pessary can occur when recommended follow-up care is neglected. 5 Ongoing care for women using pessaries involves initial assessment, correct fitting, ongoing patient education, and regular follow-up surveillance to allow modifications in management related to symptom change, early signs of potentially serious adverse effects, and/or management of pessary-related problems. This long-term care can result in significant costs to the patient and the health care system in terms of direct financial costs, time, and productivity.…”
Section: Introductionmentioning
confidence: 99%